Evaluation of the dynamic fracture characteristics of shaped-charge jets at different strain-rates and known initial LINER and EXPLOSIVE MICROSTRUCTURES - Majiet, Fakhree (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.